التأويل الصحيح للأحاديث النبوية الواردة في التكفير: نماذج تطبيقية: Appropriate Interpretation of the Prophetic Tradition Relating to al-Takfir: A Study on Some Example - Aswad, Muhammad Abdul al-Razzaq (Maʿālim al-Qurʾān wa al-Sunnah, 2018)
Takfir (Judging others as disbeliever) is a deviation from the right path and a serious social scourge that could destroy a structure of a society, ignite the flame of hatred and crumb a foundation of a state. The state thus will become disorder, unrest, left behind and underdeveloped. It resembles the biggest deviation in religiosity. Thus, this study tries to look upon the case as well as the correct interpretation of the Prophet's Hadiths about it. It will examine some of the Prophet's Hadiths relating to creed, ethics, worship, society, family, economy, crimes, politics and military. The conclusion of this study is the main reason for the presence of takfir in Islam is the false interpretation of Islamic resources. The takfir is an Islamic ruling and is Allah and His Messenger’s privilege. Wrong deeds or person with clear evidence from the revelation of its or his blasphemy is considered disbeliever otherwise he is not unless clear evidence or true conditions show it. Regarding the Prophet's hadith, somehow it has two conditions; either it is explicitly or implicitly stated and has supported from other evidence or it does not explicitly or implicitly state which is unreasonable. Therefore, it considered as false interpretation. The Prophet did mention about two types of blasphemy; first: major blasphemy, it is within a narrow range and can not be known except the person explicitly admit it. Thus, he shall forever in the hell. While the second is minor blasphemy which can be found in practics and deeds, which is the most. The doer will be considered as guilty and committed a major sin and shall be punished in the hell for a certain period.